Efficacy of medium chain triglyceride oil dietary supplementation in reducing seizure frequency in dogs with idiopathic epilepsy without cluster seizures: a non‐blinded, prospective clinical trial. (12th June 2020) - Molina, Jenifer; Jean‐Philippe, Clementine; Conboy, Lisa; Añor, Sonia; de la Fuente, Cristian; Wrzosek, Marcin Adam; Spycher, Andrea; Luchsinger, Eva; Wenger‐Riggenbach, Bettina; Montoliu, Patricia; Gandini, Gualtiero; Menchetti, Marika; et al.
Abstract : Background: Despite appropriate antiseizure drug (ASD) treatment, around two‐thirds of dogs with idiopathic epilepsy (IE) have seizures long‐term and 20–30per cent of affected dogs remain poorly controlled. Methods: The current study aim is to test in a field trial the efficacy and tolerability of a commercially available diet enriched with 6.5per cent medium chain triglyceride (MCT) oil in dogs (n=21) with at least a tier 1 idiopathic epilepsy diagnosis, without cluster seizures, in 10 veterinary practices across Europe. Each dog's quality of life (QoL), ataxia, sedation and frequency and severity of seizures were recorded by owners throughout the study. Results: The mean seizure frequency per month, averaged over the entire 84‐day study, significantly (P=0.04) decreased 32per cent compared with the baseline monthly seizure frequency recorded during the month immediately before feeding the diet. Similarly, the seizure days rate (days/month) also declined (P<0.001) by 42per cent. QoL was reported as very good to excellent (>8.5/10) in 20 of the 21 dogs before starting the diet and this remained unchanged during the trial. Conclusions: This study demonstrates the use of a diet enriched with MCTs as an adjunct to ASD treatment may have some antiseizure properties for dogs diagnosed with IE, as demonstrated in previous studies.